Effects of Different Dietary β-Glucan Levels on Antioxidant Capacity and Immunity, Gut Microbiota and Transcriptome Responses of White Shrimp (Litopenaeus vannamei) under Low Salinity - Yanbing Qiao; Li Zhou; Yayu Qu; Kunyu Lu; Fenglu Han; Erchao Li (MDPI AG, 2022)
β-Glucan could significantly improve the antioxidant capacity of aquatic animals. The effects of different dietary levels (0 (control), 0.05, 0.1, 0.2 or 0.4%) of β-glucan on the growth, survival, antioxidant capacity, immunity, intestinal microbiota and transcriptional responses of Litopenaeus vannamei under low salinity (≤3) were investigated. The dietary growth trial lasted 35 days (initial shrimp 0.26 ± 0.01 g). The results indicated that the growth performance of the 0.1% and 0.2% groups was significantly better than that of the control group. A second-order polynomial regression analysis of growth performance against dietary β-glucan indicated that the optimal dietary β-glucan level was 0.2% of dry matter. The digestive enzyme activity of the hepatopancreas was enhanced with increasing β-glucan levels. The antioxidant and nonspecific immunity capacities of the hepatopancreas were also enhanced in the 0.1% group. The α-diversity index analysis of the intestinal microbiota showed that the intestinal microbial richness of L. vannamei increased in the 0.1% group. The relative abundance of Proteobacteria decreased in the 0.1% group compared with the control group. The transcriptome results indicate that the prebiotic mechanisms of β-glucan include upregulating the expression of nonspecific immune genes and osmoregulation genes and activating KEGG pathways associated with carbohydrate metabolism under low-salinity stress. These results suggested that dietary supplementation with β-glucan markedly increased growth performance and alleviated the negative effects of low-salinity stress by contributing to the activity of biochemical enzymes and enriching carbohydrate metabolism in L. vannamei.